Onboard Scientific Observers Provide a Realistic Picture of Harvesting and Management Priorities for the Precious Red Coral (Corallium rubrum L.) - Carugati, Laura; Cau, Alessandro; Follesa, Maria Cristina; Melis, Riccardo; Moccia, Davide; Porcu, Cristina; Salvadori, Susanna; Cannas, Rita (Frontiers in Marine Science, 2020)
Mediterranean red coral Corallium rubrum is considered the most precious coral worldwide. Harvesting activities are performed by licensed scuba divers and managed through the recent pan-Mediterranean management plan issued by General Fisheries Commission for the Mediterranean (GFCM) along with measures locally enacted, imposing limits on licenses, harvesting season, minimum depth of dive and size. The use of Remotely Operated Vehicles (ROVs) is prohibited, with the only exception being for scientific purposes. Despite measures already in force, the implementation of additional management tools has been recently recommended. This paper reports results from the first monitoring campaign on C. rubrum harvesting based on ROVs for seabed exploration and Onboard Scientific Observers (OSOs), carried out from 2012 to 2015 along the coast of Sardinia (Mediterranean Sea - Western basin). More than 450 dives were monitored, confirming how ROV’ support eases the scouting of exploitable banks, leading to increases in catches. OSOs reported the collection of colonies below the minimum reference size and catches/dive above limits. Onboard observers collected data also on colony diameter, which is crucial for the estimation of population size structure and exploitation status. OSOs proved to be valid tools in providing additional and reliable information on red coral harvesting, thus deserving to be included among mandatory measures for the sustainable exploitation of red coral in the Mediterranean Sea.